A Novel Approach to Achieving End-to-End QoS for Avionic Applications - Shudrenko, Yevhenii; Plöger, Daniel; Kuladinithi, Koojana; Timm-Giel, Andreas (Electronic Communications of the EASST, 2021)
Future Internet of Things (IoT) applications, such as connected industry 4.0, become more challenging with the strict Quality of Service (QoS) requirements, including reliability and delay guarantees. Several mechanisms in the communication stack to match the expected QoS are already discussed and specified at different layers, with the goal to make the communication more reliable. They focus on the layer-specific enhancements. For example, Time-Slotted Channel Hopping (TSCH) is a link layer mechanism to avoid narrowband interference. On the network layer, several multi-path routing schemes are proposed to distribute the traffic load or to have backup paths with the purpose of making data transmissions more robust to link failures. In addition to the layer-specific improvements, an integration of the cross-layer information can guarantee an end-to-end QoS for communication in dynamic environments. In this work we propose and evaluate a cross-layer framework for cell- disjoint routing, which eliminates overlapping resource scheduling in both time and frequency. It enables the end-to-end QoS for wireless sensor networks under the IPv6 Over the TSCH Mode of IEEE 802.15.4 (6TiSCH). The proposed framework, called 6TiSCH stack with cross-layer information exchange (6TiSCH-CLX), is validated on a selected set of aviation industry applications using both simulations and analytical model.